Energy and economic prospects from the utilization of sawdust waste as biomass briquettes in East Nusa Tenggara - Nugraha, I Made Aditya; Desnanjaya, I Gusti Made Ngurah; Luthfiani, Febi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
The utilization of sawdust waste in East Nusa Tenggara has not been utilized optimally. This waste is only burned, so it sometimes causes air pollution. So there needs to be an effort to overcome these problems by making alternative energy in the form of briquettes. Analytical description method with observation, literature study and economic and energy analysis is used in this research. Sources of data in this observation came from direct observations in the field through questionnaires and interviews. Based on the data of sawdust waste produced can reach 20-60 kg per day and can be used as other forms of energy. This energy can be used as a source of electrical energy to replace conventional energy which is less environmentally friendly and fuel for burning fishery products in East Nusa Tenggara. Based on the value of the benefit-cost ratio (BCR) and payback period, good results were obtained with a value of 2.13 with a return on investment of 0.82 years. The generated electricity biomass can replace conventional electrical energy and provide cost savings of 19.2% per kWh. In addition, the utilization of this energy can have a positive impact on regional income, health, schools, and transportation as well as agriculture.